A switch from originator-adalimumab to the biosimilar SB5 in patients with Crohn's disease: an analysis of two propensity score-matched cohorts. (3rd July 2022) - Lukas, M.; Kolar, M.; Reissigova, J.; Duricova, D.; Machkova, N.; Hruba, V.; Lukas, M.; Vasatko, M.; Jirsa, J.; Pudilova, K.; Malickova, K.
Abstract: Background/aims: Originator-adalimumab, an established treatment for patients with Crohn's disease (CD), showed no difference in efficacy or adverse events versus adalimumab biosimilar SB5 (SB5-adalimumab) over 10 weeks (W) of treatment. To understand the long-term effectiveness of SB5-adalimumab in CD, patients switched from originator-adalimumab to SB5-adalimumab were compared with patients remaining on originator-adalimumab over 104 W. Methods: Data on patients aged ≥18 years, diagnosed with CD and treated at ISCARE, were collected prospectively from July 2018 to January 2021. Primary outcome: clinical disease activity at W52, measured by Harvey-Bradshaw index (HBI). Secondary outcomes: C-reactive protein (CRP), faecal calprotectin (FC) and adalimumab concentrations at W10, 26, 52 and 104, and treatment persistence. To ensure comparable cohorts, patients were propensity score (PS)-matched for age, gender and disease activity. Results: After matching, 54 patients remained per cohort. At W52, mean (SD) HBI score was 3.2 (2.5) for originator-adalimumab and 4.0 [3.6] for SB5-adalimumab (difference [95% CI] −0.78 [−2.8, 1.3]; n = 18/cohort); no clinically meaningful differences in CRP, FC or drug concentrations were noted. Kaplan–Meier's estimates (95% CI) of remaining on treatment were originator-adalimumab: 0.870 (0.785–0.965) versus SB5-adalimumab: 0.648 (0.533–0.789) at W52 and significantly lower for SB5-adalimumab versus originator-adalimumab ( p < .001) over 104 W. Local skin reaction events/pain was the main reason for treatment discontinuation in the SB5-adalimumab cohort ( n  = 20/54 [37%]). Conclusions: These long-term results of CD patients receiving originator-adalimumab or following nonmedical switch to SB5-adalimumab show similar therapeutic effects on clinical disease activity, biological parameters and pharmacokinetic profile in both cohorts from 52 to 104 W. A separation in persistence was observed beyond W26, mainly due to differences in local reactions at the injection site.